The taxonomy of Cyrtodactylus consobrinus (Peters, 1871) (Squamata, Gekkonidae) and the description of a new species from the Thai-Malay Peninsula - L. Lee Grismer; Amanda Kaatz; Jesse L. Grismer; Eddie Nguyen; Jeren J. Grergory; Perry L. Wood Jr.; Matthew L. Murdoch; Shahrul Anuar; Chan Kin Onn; Muhamad A. Muin; Parinya Pawangkhanant; Chatmongkon Suwannapoom; et al. (ZooKeys)
Phylogenetic analyses based on 1459 base pairs of the mitochondrial gene ND2 and its flanking tRNAs indicate that Cyrtodactylus consobrinus from the type locality in Sarawak, East Malaysia (Borneo) and C. consobrinus from Peninsular Malaysia are not conspecific. Both populations as well as C. hutan from East Malaysia form a strongly supported monophyletic group even though their relationships to one another remain unresolved. Cyrtodactylus consobrinus from peninsular Malaysia is described herein as the new species C. peninsularis sp. nov. whose type locality is Gunung Belumut, Johor State. Cyrtodactylus peninsularis sp. nov. is diagnosable from all other species in the malayanus group by having statistically different morphospatial positions in multiple factor analyses (MFA) based on size-corrected morphometric and meristic characters. ANOVA analyses of these characters recovered significantly different mean values between C. peninsularis sp. nov. and varying combinations of all other malayanus group species across several size-corrected morphometric and meristic characters. Genetic variation within C. peninsularis sp. nov. is geographically structured across six well supported monophyletic mitochondrial lineages bearing an uncorrected pairwise sequence divergence ranging from 0.97–4.5%. Despite its well supported phylogeographic structure, PCAs and ANOVAs recovered statistically weak morphological separation among the lineages and as such, all are considered conspecific pending a genomic analysis. The phylogeographic structure within the forest-dwelling C. peninsularis sp. nov. is quite similar to that of the stream-adapted ranid frog genus Amolops and less so to that of the microhabitat specialists of the C. pulchellus group and the forest generalist C. quadrivirgatus, all of whom are sympatric across Peninsular Malaysia.